Rumen-Reticular Temperature During Estrus and Ovulation Using Automated Activity Monitors in Dairy Cows - Burnett, Tracy A.; Kaur, Manveen; Polsky, Liam; Cerri, Ronaldo L. A. (Frontiers in Veterinary Science, 2020)
This study aimed to determine changes in rumen-reticular temperature (RRT) at estrus or ovulation and determine if these changes are associated with the intensity of estrous expression. Cows were equipped with an automated activity monitor (AAM) and a rumen-reticular bolus thermometer. A total of 190 estrus episodes were used where physical activity data was recorded using the AAM and ovulation was determined via ultrasonography at alert and twice daily, for a maximum of 60 h. Estrous expression was assessed using the maximum activity and duration in which activity remained above the AAM threshold; both characteristics were categorized using the median. Temperature data was collected for the duration of estrus, as well as for the interval of time where ovulation was determined to occur. Three measures of temperature were calculated: 1) positive area under the curve (AUC), 2) maximum positive temperature change (PTC), 3) maximum negative temperature change (NTC) at estrus (AUCE/ PTCE/ NTCE) and around ovulation (AUCO/PTCO/ NTCO). Both AUC and PTC were greater during estrus than around ovulation (2.7 ± 0.2 and 1.1 ± 0.3 °C2 for AUCE and AUCO; 0.55 ± 0.03 and 0.26 ± 0.04 °C for PTCE and PTCO, respectively). In contrast, NTC was lower around ovulation than estrus (-0.28 ± 0.05 and -0.60 ± 0.06 °C for NTCE and NTCO). Cows with greater estrous expression had greater AUC and PTC during estrus than around ovulation, but cows with lesser estrous expression had similar AUC and PTC. Increases in AUC (High THI (Temperature Humidity Index): High activity: 4.7 ± 0.5, Low activity: 1.5 ± 0.4; Low THI: High activity: 3.1 ± 0.2, Low activity: 1.4 ± 0.2 °C2) and PTC (High THI: High activity: 0.79 ± 0.08, Low activity: 0.36 ± 0.07; Low THI: High activity: 0.60 ± 0.04, Low activity: 0.47 ± 0.04 °C) associated with estrous expression were found to be greater on days with higher THI. Alerts created using standard deviations from the mean were unable to detect estrus or ovulation with acceptable precision. Further research is required to determine how changes in RRT can be used successfully to predict estrus and ovulation.